Integrated Excitatory/Inhibitory Imbalance and Transcriptomic Analysis Reveals the Association between Dysregulated Synaptic Genes and Anesthetic-Induced Cognitive Dysfunction - Yasheng Yan; Sarah Logan; Xiaojie Liu; Bixuan Chen; Congshan Jiang; Thiago Arzua; Ramani Ramchandran; Qing-song Liu; Xiaowen Bai (Cells, 2022)
Emerging evidence from human epidemiologic and animal studies has demonstrated that developmental anesthesia neurotoxicity could cause long-term cognitive deficits and behavioral problems. However, the underlying mechanisms remain largely unknown. We conducted an electrophysiological analysis of synapse activity and a transcriptomic assay of 24,881 mRNA expression on hippocampal tissues from postnatal day 60 (P60) mice receiving propofol exposure at postnatal day 7 (P7). We found that developmentally propofol-exposed P60 mouse hippocampal neurons displayed an E/I imbalance, compared with control mice as evidenced by the decreased excitation and increased inhibition. We found that propofol exposure at P7 led to the abnormal expression of 317 mRNAs in the hippocampus of P60 mice, including 23 synapse-related genes. Various bioinformatic analyses revealed that these abnormally expressed synaptic genes were associated with the function and development of synapse activity and plasticity, E/I balance, behavior, and cognitive impairment. Our findings suggest that the altered E/I balance may constitute a mechanism for propofol-induced long-term impaired learning and memory in mice. The transcriptomic and bioinformatic analysis of these dysregulated genes related to synaptic function paves the way for development of therapeutic strategies against anesthetic neurodegeneration through the restoration of E/I balance and the modification of synaptic gene expression.